2019
DOI: 10.1155/2019/9832075
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Knowledge, Intention to Practice and Predictors among Primiparous Women in Enugu South-East, Nigeria

Abstract: Breastfeeding is considered as the most complete nutritional source for infants because breast milk contains the essential carbohydrates, fats, proteins, and immunological factors needed for infants to thrive and resist infection in the formative first year of life. Knowledge of exclusive breastfeeding (EBF) among women is essential when promoting optimal breastfeeding practices. This cross-sectional descriptive survey assessed knowledge and intention to practice EBF and its associated factors during pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
30
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
15
30
3
2
Order By: Relevance
“…In this study maternal age had no association with the practice of exclusive breastfeeding. Similar finding was reported in a previous study done in Sagamu (22).There are conflicting reports on the influence of maternal educational status on breastfeeding practice (12,23,(33)(34)(35). In this study maternal educational status had no association with the practice of exclusive breastfeeding; similar finding was reported by researchers in Sokoto, north-west Nigeria (28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study maternal age had no association with the practice of exclusive breastfeeding. Similar finding was reported in a previous study done in Sagamu (22).There are conflicting reports on the influence of maternal educational status on breastfeeding practice (12,23,(33)(34)(35). In this study maternal educational status had no association with the practice of exclusive breastfeeding; similar finding was reported by researchers in Sokoto, north-west Nigeria (28).…”
Section: Discussionsupporting
confidence: 91%
“…In this study maternal educational status had no association with the practice of exclusive breastfeeding; similar finding was reported by researchers in Sokoto, north-west Nigeria (28). In Enugu, south-east Nigeria, mothers that attained tertiary level of educational were found to be more likely to breastfeed exclusively when compared with those with lower educational attainment (33). Similar finding was reported by Ogbo et al (34).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, this study revealed that mothers with higher levels of education were signi cantly associated reduced levels of EBF practice in both urban and rural areas. This agrees with earlier literature, as mothers with lower levels of education are more likely to breastfeed their infants exclusively than those with higher levels of education [22][23][24][25][26][27][28][29][30]. This may be attributed to the fact that mothers with higher levels of education are likely to be engaged in the formal employment sector, which does not avail them with ample time and strength to adopt EBF practice.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, a study revealed that 76.4% of mothers practiced EBF for a period of 4-6months, 38.2% initiated breastfeeding within 30 minutes and 33.2% within an hour, while few breastfed on demand [25]. Also, age, educational attainment, EBF knowledge and sources of information about EBF are to be signi cant predictor of good intention to practice EBF [27]. In addition, rural mothers with low socioeconomic status, early initiation of breastfeeding and delivery assistance have been shown to be more likely to practice EBF [28].…”
Section: Introductionmentioning
confidence: 99%
“…Kazaura's work in Tanzania has similar results to ours 14 . These results differ from those of Ihudiebube-Splendor et al in Nigeria, who showed that neither age, marital status, nor profession were associated with a satisfactory level of knowledge of EBF 28 . This difference is explained by the fact that our study concerned all women, unlike Ihudiebube-Splendor, who worked only with primiparas.…”
Section: Sociodemographic Characteristicscontrasting
confidence: 99%